Erpobdellid leeches (Annelida, Clitellata, Hirudinida) from Tunisia: New records with the description of a new Trocheta species - Ahmed, Raja Ben; Bielecki, Aleksander; Cichocka, Joanna M.; Tekaya, Saïda; Gorzel, Małgorzata; Harrath, Abdul Halim (Zootaxa, 2013)
Up to now in Tunisia, freshwater Hirudinida are represented by two mainly haematophagous families: Hirudinidae and Glossiphonidae, and a predatory one: the family Erpobdellidae. The present study provides new information on the diver-sity and taxonomy of erpobdellid leeches. Identification was based, in addition to morphological data, on the length of sperm ducts and the lengths of ovisacs in relation to the neurosomite (ns) and on the shape and size of the male atrium. Five taxons are found. Two subspecies are reported for the first time in the country: Dina punctata punctata Johansson, 1927 and Dina punctata maroccana Nesemann and Neubert, 1994. Tunisian populations of two species, Erpobdella tes-tacea (Savigny, 1820) and Trocheta africana Nesemann and Neubert, 1994, are described, with records of new localities. The new Trocheta tunisiana n. sp. is discovered and described in detail. Trocheta species live in springs in elevated areas while Erpobdella seem to prefer low altitude reservoirs. A comprehensive comparison of the three genera is presented. The disparity between the actual systematics and phylogeny is discussed. This study gives also a detailed distribution of the five species in the north of Tunisia with notes on ecological preference of the genus Dina. Finally a key for the deter-mination of freshwater erpobdellid species from Tunisia is proposed.